Diagnostic uncertainties in congenital syphilis: A case report - Niharika Khanal; Srijana Basnet; Daman Raj Paudel; Vivek Karn; Sunita Tamang; Jasmine Shakya; Newton Ashish Shah (Clinical Case Reports, 2024)
Key Clinical Message Congenital syphilis is a forgotten disease, and often misdiagnosed. It can present with a myriad of clinical features, mimicking various other conditions therefore posing difficulty in diagnosis. Patient may be born preterm with low birth weight, failure to thrive with hemolytic anemia, thrombocytopenia, and leukocytosis. It is a treatable condition, commonly treated with penicillin or ceftriaxone.